Global caregiver concerns of SARS-CoV-2 vaccination in children with cancer: a cross-sectional mixed-methods study. (19th May 2023) - Gumy, Julia M.; Silverstein, Allison; Kaye, Erica C.; Caniza, Miguela A.; Homsi, Maysam R.; Pritchard-Jones, Kathy; Bate, Jessica M.; ,
Abstract: The objective of this study was to understand global caregiver concerns about SARS-CoV-2 vaccination for children with cancer and to provide healthcare providers with guidance to support parental decision-making. A co-designed cross-sectional mixed-methods survey was distributed to primary caregivers of children with cancer globally between April and May 2021 via several media. Caregivers were asked to rate the importance of vaccine-related questions and the median scores were ranked. Principal Component Analysis was conducted to identify underlying dimensions of caregiver concerns by World Bank income groups. Content analysis of free-text responses was conducted and triangulated with the quantitative findings. 627 caregivers from 22 countries responded to the survey with 5.3% ( n = 67) responses from low-and-middle-income countries (LMIC). 184 caregivers (29%) provided free-text responses. Side effects and vaccine safety were caregivers' primary concerns in all countries. Questions related to logistics were of concern for caregivers in LMIC. A small minority of caregivers ( n = 17) did not consider the survey questions important; free-text analysis identified these parents as vaccine hesitant, some of them quoting safety and side effects as main reasons for hesitancy. Healthcare providers and other community organizations globally need to provide tailored information about vaccine safety and effectiveness in pediatric oncology settings. Importantly, continued efforts are imperative to reduce global inequities in logistical access to vaccines, particularly in LMIC.